Evolution of the Toarcian (Early Jurassic) carbon-cycle and global climatic controls on local sedimentary processes (Cardigan Bay Basin, UK) - Xu, Weimu; Ruhl, Micha; Jenkyns, Hugh C.; Leng, Melanie J.; Huggett, Jennifer M.; Minisini, Daniel; Ullmann, Clemens V.; Riding, James B.; Weijers, Johan W.H.; Storm, Marisa S.; Percival, Lawrence M.E.; Tosca, Nicholas J.; et al. (Elsevier, 2018)
The late Early Jurassic Toarcian Stage represents the warmest interval of the Jurassic Period, with an abrupt rise in global temperatures of up to ∼7 °C in mid-latitudes at the onset of the early Toarcian Oceanic Anoxic Event (T-OAE; ∼183 Ma). The T-OAE, which has been extensively studied in marine and continental successions from both hemispheres, was marked by the widespread expansion of anoxic and euxinic waters, geographically extensive deposition of organic-rich black shales, and climatic and environmental perturbations. Climatic and environmental processes following the T-OAE are, however, poorly known, largely due to a lack of study of stratigraphically well-constrained and complete sedimentary archives. Here, we present integrated geochemical and physical proxy data (high-resolution carbon-isotope data (δ13C), bulk and molecular organic geochemistry, inorganic petrology, mineral characterisation, and major- and trace-element concentrations) from the biostratigraphically complete and expanded entire Toarcian succession in the Llanbedr (Mochras Farm) Borehole, Cardigan Bay Basin, Wales, UK. With these data, we (1) construct the first high-resolution biostratigraphically calibrated chemostratigraphic reference record for nearly the complete Toarcian Stage, (2) establish palaeoceanographic and depositional conditions in the Cardigan Bay Basin, (3) show that the T-OAE in the hemipelagic Cardigan Bay Basin was marked by the occurrence of gravity-flow deposits that were likely linked to globally enhanced sediment fluxes to continental margins and deeper marine (shelf) basins, and (4) explore how early Toarcian (tenuicostatum and serpentinum zones) siderite formation in the Cardigan Bay Basin may have been linked to low global oceanic sulphate concentrations and elevated supply of iron (Fe) from the hinterland, in response to climatically induced changes in hydrological cycling, global weathering rates and large-scale sulphide and evaporite deposition.